USING MNEMONICS TO IMPROVE MEMORY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Mnemonics are learning techniques aimed at improving memory functions by better organizing and processing learning through effective encoding and retrieval processes. Currently, mnemonic techniques and methods increasingly attract attention as effective tools in educational and clinical practices due to their high effectiveness in improving short- and long-term memory functions in people of various age brackets. Recent studies clearly show that acronyms, the method of loci, musical mnemonic methods, serious games-based mnemonic training tools, and those based on virtual reality increase learning effectiveness and memory functions by a significant factor. In addition to learning and memory functions, research studies point to the importance of mnemonic techniques and methods in treating seniors and people with memory-related problems by improving connectivity and functional memory functions. This paper examines the theoretical aspects of mnemonic learning techniques and their effectiveness from recent research and practical ways of application in educational and learning practices related to their functions and effectiveness. The results show that the application of systematic mnemonic methods not only enhances memory functions but also motivates learners significantly. Using mnemonic techniques and methods within educational practices shows effectiveness in improving memory functions and overall efficiency in learning and memory processes.